Answer:
f(-3) = -3
Explanation:
Step 1: f(x) means "f of x" and f(-3) means "f of -3", so you have to replace all the "x" letters in the function with the value -3.
![f(x)=x^4+3x^3-x^2+6\\f(-3)=(-3)^4+3(-3)^3-(-3)^2+6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/86sls7rfy34qh2qbzknwxvlxa8236antia.png)
Step 2: Apply the exponents. Make sure you remember to put in the -3 and not just 3.
![f(-3)=81+3(-27)-9+6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mfer0sq73m312x4hsz5e45hwio9sgmdxwi.png)
Step 3: Use BEDMAS rules to complete the calculation.
![f(-3)=81-81-9+6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5mf5pfalygz6q2bvvmim47ue0d4vq8tip7.png)
![f(-3)=-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hu725m0ilsivq5esd4tjjtmrlfaqqegzte.png)
Therefore the answer is f(-3) = -3.